No Plasmatic Proteomic Signature at Clinical Disease Onset Associated With 11 Year Clinical, Cognitive and MRI Outcomes in Relapsing-Remitting Multiple Sclerosis Patients - Bridel, Claire; Eijlers, Anand J. C.; van Wieringen, Wessel N.; Koel-Simmelink, Marleen; Leurs, Cyra E.; Schoonheim, Menno M.; Killestein, Joep; Teunissen, Charlotte E. (Frontiers in Molecular Neuroscience, 2018)
Background The clinical course of relapsing-remitting multiple sclerosis (RRMS) is highly heterogeneous and prognostic biomarkers at time of diagnosis are lacking. Objective We investigated the predictive value of the plasma proteome at time of diagnosis in RRMS patients. Methods The plasma proteome was interrogated using a novel aptamer-based proteomics platform, which allows to measure the levels of a predefined set of 1310 proteins. Results In 67 clinically and radiologically well characterised RRMS patients, we found no association between the plasma proteome at diagnosis and clinical, cognitive or MRI outcomes after 11 years. Conclusions Reasons for this may include the selected cohort, proteomics platform or matrix, but could also reflect the largely unpredictable nature of RRMS.